2021
DOI: 10.3390/ma14133447
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Laser Defocusing in Selective Laser Melted IN 625

Abstract: Laser defocusing was investigated to assess the influence on the surface quality, melt pool shape, tensile properties, and densification of selective laser melted (SLMed) IN 625. Negative (−0.5 mm, −0.3 mm), positive (+0.3 mm, +0.5 mm), and 0 mm defocusing distances were used to produce specimens, while the other process parameters remained unchanged. The scanning electron microscopy (SEM) images of the melt pools generated by different defocusing amounts were used to assess the influence on the morphology and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Supplementary method 3) measurements were performed with similar beam sizes having an opposite defocusing position (positive and negative as divergent and convergent beams, respectively) and different laser intensity distribution. In conduction mode, the melt pool dimensions proved to be similar under identical laser processing parameters with a slight increase in melt pool depth and length in positive defocus, in agreement with previous observations 52,53 . Upon transition from conduction to keyhole, a signi cant difference in the melt pool length is observed with 45% higher values in RM2 compared to RM6.…”
Section: Operando Observation Of the Thermo-mechanical Instabilitiessupporting
confidence: 90%
“…Supplementary method 3) measurements were performed with similar beam sizes having an opposite defocusing position (positive and negative as divergent and convergent beams, respectively) and different laser intensity distribution. In conduction mode, the melt pool dimensions proved to be similar under identical laser processing parameters with a slight increase in melt pool depth and length in positive defocus, in agreement with previous observations 52,53 . Upon transition from conduction to keyhole, a signi cant difference in the melt pool length is observed with 45% higher values in RM2 compared to RM6.…”
Section: Operando Observation Of the Thermo-mechanical Instabilitiessupporting
confidence: 90%
“…The appropriate laser spot size should provide sufficient energy density to melt the current powder layer and fuse to the previously melted one, but also to be small enough to meet requirements of the dimensional precision and surface roughness [ 17 ]. The effects of laser spot size, on various characteristics of SLM builds, have been investigated by a limited number of studies [ 17 , 18 , 19 , 20 , 21 , 22 ]. Change of laser spot size, through focal shift, would affect the laser energy density, porosity, and microstructure of the Inconel 718 alloy; a finer microstructure is found for a smaller laser spot [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that a good surface finish in SLM builds of AlSi12 alloy can be obtained with an optimal combination of defocus distance and laser power [ 21 ]. In the study of SLM builds of IN 625 alloy [ 22 ], the surface roughness is increased, with increasing laser spot diameter, but the tensile strength is barely affected by the laser spot size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the research by Paraschiv et al [2], laser defocusing in the selective laser melting (SLM) process (powder bed fusion, PBF) was investigated to assess the influence on the surface quality, melt pool shape, tensile properties, and densification of the produced samples (IN 625 material). It was observed that the melting height increased while the melting depth decreased from positive to negative defocusing.…”
mentioning
confidence: 99%